Incidence and severity of SARS-CoV-2 infection and vaccine BNT162 side effects in children and adolescents with Noonan Syndrome: a national multicentric study - Dal Ben, Sarah; Tamburrino, Federica; Bonomo, Francesca; Scarano, Emanuela; Orlandini, Eleonora; Pozzobon, Gabriella; Giavoli, Claudia; Corezzola, Chiara; Faienza, Maria Felicia; Patti, Giuseppa; Capalbo, Donatella; Salerno, Mariacarolina; et al. (Frontiers in Pediatrics, 2026)
BackgroundPre-existing medical conditions are known to increase the risk of severe coronavirus disease 2019 (COVID-19), even in pediatric populations. This study aimed to evaluate the symptoms and severity of COVID-19, as well as the side effects of the BNT162 vaccine, in children and adolescents with Noonan Syndrome (NS) compared to healthy controls.MethodsA retrospective and prospective multicenter study was conducted across Italy. Clinical characteristics, course, and duration of SARS-CoV-2 infection, as well as side effects of the BNT162 vaccine, were compared between 97 patients with NS and 97 age- and sex-matched healthy subjects.ResultsNo statistically significant differences were found in the severity or duration of COVID-19 between NS patients and controls. NS patients exhibited a higher rate of rhinorrhea during SARS-CoV-2 infection (69.2% vs. 46%, p < 0.05), whereas anosmia was more common among controls (1.5% vs. 12.7%, p < 0.05). No statistically significant differences in side effects from the BNT162 vaccine were observed between groups. 95% confidence intervals were calculated for key outcomes to improve comparability.ConclusionChildren and adolescents with Noonan Syndrome generally experience a mild course of COVID-19 and show no evidence of increased vaccine-related risk. Despite the small sample size and the rarity of severe events, these findings yield valuable insights for patients living with this rare disease.